«Мягкая Сила» Как Главный Аспект Внешней Политики Султаната Оман - Л.с, Чикиева (Океанский менеджмент, 2026)
The article traces the multifaceted path of the Sultanate of Oman: it analyzes the evolution of the Sultanate's role: from a British possession focused on domestic politics and the resolution of internecine wars to an influential player in the region and a mediator in resolving conflicts on an international scale. The article shows how Oman combines a traditional but unique foreign policy with active participation in solving global problems, and neutral, as a peacemaker and mediator in terms of escalating conflicts.
Keywords: Oman – Histoire

تاريخ عمان: من الاستيطان البشري إلى نهاية الدولة الإباضية - القاسمي, سلطان بن محمد (منشورات القاسمي, 2023)
Keywords: Imamat – Oman; Oman – Histoire

ثقافة العمانيين وتواصلهم عبر التاريخ - النوفلي, حميد بن سيف (وزارة التربية و التعليم, 2010)
Keywords: Oman – Histoire

Qalhāt - Bhacker, Mohammed Reda; Bhacker, Bernadette (Encyclopaedia of Islam Three Online, 2024)
Keywords: Oman – Histoire

عمان منذ 1856م.. مسيرا ومصيرا - Landen, Robert Geran (وزارة التراث والثقافة, 2016)
Keywords: Oman – Histoire

‏دراسات في التاريخ سلطنة عمان المعاصر - الجبارات, محمود (‏دار الرافدين, 2023)
Keywords: Oman – Histoire

عمان عبر التاريخ - السيابي, سالم بن حمود (وزارة التراث القومي والثقافة, 2001)
Keywords: Oman – Histoire

عمان عبر التاريخ - السيابي, سالم بن حمود (وزارة التراث القومي والثقافة, 2001)
Keywords: Oman – Histoire

عمان عبر التاريخ - السيابي, سالم بن حمود (وزارة التراث القومي والثقافة, 2001)
Keywords: Oman – Histoire

عمان عبر التاريخ - السيابي, سالم بن حمود (وزارة التراث القومي والثقافة, 2001)
Keywords: Oman – Histoire

Chronologie indicative : de Magan à la Nahda - Maguer-Gillon, Sterenn le; Sebiane, Maho (Arabian Humanities, 2022)
IIIe millénaire av. J.-C. Ca. 3100 – 2700 av. J.-C. Culture de Hafit. Ca. 2700 – 2000 av. J.-C. Culture d’Umm an-Nar. Ca. 2400 av. J.-C. Le pays de Magan, identifié comme Oman, apparaît dans les textes cunéiformes sumériens. Commerce du cuivre, du bois et de la diorite. Échanges entre l’Inde et la Mésopotamie. Ca. 2000 – 1300 av. J.-C. Culture de Wādī Sūq. IIe millénaire av. J.-C. Ca. 1200 av. J.-C. Site de Salut. IIIe siècle av. J.-C. Fondation du port de Sumhuram, dans le Dhofar, comptoir ...
Number: 15
Keywords: Oman – Histoire

Oman au fil du temps : Une nation de la Nahda à l’Oman Vision 2040 - Sebiane, Maho; Breteau, Marion; Maguer-Gillon, Sterenn le (Arabian Humanities, 2022)
L’ambition de ce dossier thématique est d’esquisser un état des lieux pluridisciplinaire de la période contemporaine du Sultanat d’Oman. Il a été envisagé comme une invitation à faire dialoguer des réflexions de recherche issues d’horizons divers portant sur l’histoire de ce pays, mais également sur les grandes mutations sociales et culturelles qui ont traversé sa société. L’appel à contribution a été lancé au début de l’année 2020 dans un contexte qui ne présageait pas de la crise du coronav...
Number: 15
Keywords: Oman – Histoire

A History of the al-΄Ain / Buraimi Oasis - Power, Timothy (2012)
Keywords: Oman – Histoire

Historical Landscapes - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
Omani civilization is very old. Early Bronze Age civilization in the fourth millennium BC unified the whole Oman peninsula from the Abu Dhabi islands to Ra’s al-Hadd and Masirah Island. Coastal regions were in constant touch with the outside world as boats, loaded with copper, diorite and frankincense travelled far, from the south-eastern shores of Africa along the coast of the Indian Ocean rim. In contrast, villages in the Hajar mountains formed isolated pockets in the valleys and on the slopes of the mountains. Regardless, the irrigation was a matter for the village where agreements over irrigation systems were negotiated and managed on a customary basis. The governing power, whether it was a religious Imam, a secular king, a sultan or a foreign occupier, was a factor in the village reality. At times this was beneficial, as under the First unitary Imamate in the eighth to ninth century, when customary law and Islamic law on irrigation were consolidated into a harmonised whole. At times, the collapse of central power and subsequent internal fighting between the tribes resulted in significant destruction and the abandonment of settlement. The birth of a modern Omani state in the latter half of the twentieth century under Sultan Qaboos signalled a break with the past, except for the culture, which continues to live in the traditions and laws of the people of the land.
Keywords: Oman – Histoire

مقدمة تاريخ أئمة وسادة عمان - Badger, George Percy (وزارة التراث والثقافة, 2012)
Keywords: Oman – Histoire

Oman as pole of cultural, mercantile and economic business between east and west - Piacentini Fiorani, Valeria (Istituto Lombardo - Accademia di Scienze e Lettere - Incontri di Studio, 2017)
Keywords: Oman – Histoire

ʿUmān ʿabra ‘l-Tārīkh - Sitālī, Abū Bakr Aḥmad b. Saʿīd al-Kharūṣī al- (Ministry of National Heritage and Culture, 2001)
Keywords: Oman – Histoire

ʿUmān ʿabra ‘l-Tārīkh - Sitālī, Abū Bakr Aḥmad b. Saʿīd al-Kharūṣī al- (Ministry of National Heritage and Culture, 2001)
Keywords: Oman – Histoire

ʿUmān ʿabra ‘l-Tārīkh - Sitālī, Abū Bakr Aḥmad b. Saʿīd al-Kharūṣī al- (Ministry of National Heritage and Culture, 2001)
Keywords: Oman – Histoire

ʿUmān ʿabra ‘l-Tārīkh - Sitālī, Abū Bakr Aḥmad b. Saʿīd al-Kharūṣī al- (Ministry of National Heritage and Culture, 2001)
Keywords: Oman – Histoire

al-Makāna al-Tārīkhiyya li-Wilāyat Qurayyāt - Akhzamī, Saʿīd b. Sālim al- (al-Qurayyāt ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī’l-Fatra min 4-5 Dhū ‘l-Ḥijja 1427 H. al-muwāfiq 25-26 Dīsimbir 2006, 2008)
Keywords: Oman – Histoire

al-Makāna al-Tārīkhiyya li-Wilāyat Shināṣ - Daramkī, Sayf b. Muḥammad (Shināṣ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Shināṣ Yawmay al-ithnayn wa’l-thulathā’ 11 wa-12 Dhū ‘l-Qaʿda (sic) al-muwāfiq 10 wa-11 Nūfimbir 2008, 2010)
Keywords: Oman – Histoire

al-Makāna al-Tārīkhiyya li-Wilāyat al-Muḍaybī - Ẓafrī, Saʿīd b. Sulaymān b. Subayḥ al- (al-Muḍaybī ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat al-Muḍaybī Yawmay al-Aḥad wa’l-Ithnayn 21 wa-22 Dhū ‘l-Ḥijja al-muwāfiq 30 wa-31 Dīsimbir 2007, 2010)
Keywords: Oman – Histoire

al-Makāna al-Tārīkhiyya li-Wilāyat Mirbāṭ - ʿAmrī, Saʿīd b. Khālid al- (Mirbāṭ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Mirbāṭ Yawm al-ithnayn wa’l-thulathā’ 27-28 Shawwāl 1432 H. al-muwāfiq 26-27 Sibtimbar 2011, 2012)
Keywords: Oman – Histoire

Tārīkh ʻUmān al-ḥadīth: dirāsah fī al-ʻalāqāt al-iqlīmīyah wa-al-dawlīyah, 1789-1904 M - Wasmī, Khālid al- (ʻAyn lil-Dirāsāt wa-al-Buḥūth al-Insānīyah wa-al-Ijtimāʻīyah, 2004)
Keywords: Oman – Histoire

Dirāsāt fī Tārīkh ʿUmān - Fawzī, Fārūq ʿUmar (Jāmiʿat Āl al-Bayt, 2000)
Keywords: Oman – Histoire

ʿAlāqāt ʿUmān bi’l-ʿĀlamayni al-ʿArabī wa’l-Islāmī - ʿUbaydāt, Dāwud; Abū Salīm, ʿAlī (Aʿmāl al-Multaqà al-ʿIlmi al-awwal ḥawla Turāth Salṭanat ʿUmān al-Shaqīqa Qadīman wa-Ḥadīthan, 2002)
Keywords: Oman – Histoire

A History of Modern Oman - Jones, Jeremy; Ridout, Nicholas Peter (Cambridge University Press, 2015)
Keywords: Oman – Histoire

Oman: the Islamic democratic tradition - Ghabbāsh, Ḥusayn (Routledge, 2006)
Keywords: Oman – Histoire

مدينة نزوى في عهد الامامة الاباضية الثانية (177-280هـ/793-893م): دراسة تاريخية و حضارية - السليماني, عبد الرحمن بن أحمد (جامعة السلطان قابوس, 2006)
Keywords: Oman – Histoire

عمان: الديمقراطية الاسلامية: تقاليد الامامة والتاريخ السياسي الحديث (1500-1970) - غباش, حسين عبيد (الفرابي, 2006)
Keywords: Oman – Histoire

كتاب عمان تاريخ وأمجاد :‏ ‏تاريخ وأمجاد عمان على مر العصور التاريخية حتى عصرنا الحديث - تركي, برغش بن سعيد (دار مجان, 2012)
Keywords: Oman – Histoire

الموجز في التاريخ العماني - البوسعيدي, سالم بن سعيد (دار الجيل, 2015)
Keywords: Oman – Histoire

مدينة نزوى في عهد الإمامة الإباضية الثانية (177-28-هـ/793-893م) :‏ ‏دراسة تاريخية وحضارية - السليماني, عبد الرحمن بن أحمد (بيت الغشام, 2019)
Keywords: Oman – Histoire

A Historian at the Edge: Muḥammad ibn ʿAbd Allāh al-Sālimī’s Twentieth-Century - Coppola, Anna Rita (Today's perspectives on Ibadi history, 2017)
Keywords: Oman – Histoire